Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Materi Sistem Persamaan Linear Dua Variabel Ditinjau dari Kemampuan Awal Matematika - Hamzah Upu; Awi Dassa; Nurhalizah R (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2022)
This research aims to analyze students’ errors and the factors that cause students’ errors in solving problems of two-variable linear equations system based on Newman’s stages viewed from initial mathematical ability. This research is qualitative research with a descriptive approach. The subject of this research is students grade IX that consists of six students which two people for each level of initial mathematical ability. Data collection techniques in this research are test and interview. The research instrument was used, namely the initial mathematical ability test, a diagnostic test of a two-variable linear equation system, and interview guidelines. The data analysis techniques in this study include the condensation of data, the presentation of data, and the verification or drawing of conclusions. The result shows that: (1) Students with high initial mathematical abilities make mistakes in processing skills and writing in answers; (2) Students with medium early mathematical abilities are making mistakes in understanding questions, transforming questions, processing skills, and writing answers; (3) Students with low initial mathematical abilities make errors in reading questions, misunderstanding questions, transformation, processing skills, and writing answers. The factors that most often cause students' errors in solving the Two-Variable Linear Equations System material problems are students being less thorough and hastily working on the questions, have not mastered the prerequisite material, and as the result of previous mistakes.